Purification and Characterization of a Novel Intracellular Sucrase Enzyme of Leishmania donovani Promastigotes - Arpita Singh; Debjani Mandal (Biochemistry Research International)
The promastigote stage of Leishmania resides in the sand fly gut, enriched with sugar molecules. Recently we reported that Leishmania donovani possesses a sucrose uptake system and a stable pool of intracellular sucrose metabolizing enzyme. In the present study, we purified the intracellular sucrase nearly to its homogeneity and compared it with the purified extracellular sucrase. The estimated size of intracellular sucrase is ~112 kDa by gel filtration chromatography, native PAGE, and substrate staining. However, in SDS-PAGE, the protein is resolved at ~56 kDa, indicating the possibility of a homodimer in its native state. The kinetics of purified intracellular sucrase shows its higher substrate affinity with a Km of 1.61 mM than the extracellular form having a Km of 4.4 mM. The highly specific activity of intracellular sucrase towards sucrose is optimal at pH 6.0 and at 30°C. In this report the purification and characterization of intracellular sucrase provide evidence that sucrase enzyme exists at least in two different forms in Leishmania donovani promastigotes. This intracellular sucrase may support further intracellular utilization of transported sucrose.